Cechy języka Hieronima Floriana Radziwiłła (na podstawie wybranych rękopisów) - Zawilska, Katarzyna (Acta Polono-Ruthenica, 2018)
Hieronim Florian Radziwiłł (1715–1760) was one of the most powerful magnates of PolishLithuanian Commonwealth, the owner of residencies in Biała (now Biała Podlaska) and Słuck. Historians point out on the one hand his achievements as a patron of art, founder of a ballet school and a supporter of a few theatres but on the other hand they describe him as an eccentric and cruel person for his serfs. The prince left rich written heritage (diaries, messages, letters) which is an invaluable source for study on the author’s idiolect. The aim of the paper is to show the most important features of Radziwił’s writing with the emphasis on eastern elements of the language on the basis of chosen manuscripts kept in Czartoryscy Library in Kraków.